Comparative Immunogenicity of Enhanced Seasonal Influenza Vaccines in Older Adults: A Systematic Review and Meta-analysis. (14th December 2018) - Ng, Tiffany W Y; Cowling, Benjamin J; Gao, Hui Zhi; Thompson, Mark G
Abstract : In a review of 39 immunogenicity trials with adults aged ≥60 years, enhanced (high dose, MF59-adjuvanted, and intradermal) influenza vaccines had significantly higher postvaccination titers (for all vaccine strains); differences between vaccine types were most notable for A(H3N2). Abstract: Background: A number of enhanced influenza vaccines have been developed for use in older adults, including high-dose, MF59-adjuvanted, and intradermal vaccines. Methods: We conducted a systematic review examining the improvements in antibody responses measured by the hemagglutination inhibition assay associated with these enhanced vaccines, compared with each other and with the standard-dose (SD) vaccine using random effects models. Results: Thirty-nine trials were included. Compared with adults aged ≥60 years receiving SD vaccines, those receiving enhanced vaccines had significantly higher postvaccination titers (for all vaccine strains) and higher proportions with elevated titers ≥40 (for most vaccine strains). High-dose vaccine elicited 82% higher postvaccination titer to A(H3N2) compared with SD vaccine; this was significantly higher than the 52% estimated for MF59-adjuvanted versus SD vaccines ( P = .04), which was higher than the 32% estimated for intradermal versus SD vaccines ( P < .01). Conclusions: Overall, by summarizing current evidence, we found that enhanced vaccines had greater antibody responses than the SD vaccine. Indications of differences among enhanced vaccines highlight the fact that further research is needed to compare new vaccine options, especially during seasons with mismatched circulating strains and for immune outcomes other than hemagglutination inhibition titers as well as vaccine efficacy.